A Multi-faceted Approach to Achieving the Global Acceptance of Animal-free Research Methods. Issue 5 (October 2016) - Melbourne, Jodie; Bishop, Patricia; Brown, Jeffrey; Stoddart, Gilly
In 2015, the PETA International Science Consortium Ltd. was awarded the Lush Training Prize for its broad approach to education and training on the effective use of human-relevant, non-animal research techniques. The prize was awarded for work that included hosting workshops and webinars, initiating in-person training sessions and developing educational resources. The Consortium works closely with industry and regulatory agencies to identify and overcome barriers to the validation and use of alternatives to animal testing, by using an approach that identifies, promotes and verifies the implementation of these methods. The Consortium's recent activities toward replacing tests on animals for nanomaterials, pesticides and medical devices, are described, as examples of projects with broad applicability aimed at large-scale regulatory change.